Basic mechanisms and kinetics of pause-interspersed transcript elongation. Issue 1 (16th December 2020) - Qian, Jin; Dunlap, David; Finzi, Laura
Abstract: RNA polymerase pausing during elongation is an important mechanism in the regulation of gene expression. Pausing along DNA templates is thought to be induced by distinct signals encoded in the nucleic acid sequence and halt elongation complexes to allow time for necessary co-transcriptional events. Pausing signals have been classified as those producing short-lived elemental, long-lived backtracked, or hairpin-stabilized pauses. In recent years, structural microbiology and single-molecule studies have significantly advanced our understanding of the paused states, but the dynamics of these states are still uncertain, although several models have been proposed to explain the experimentally observed pausing behaviors. This review summarizes present knowledge about the paused states, discusses key discrepancies among the kinetic models and their basic assumptions, and highlights the importance and challenges in constructing theoretical models that may further our biochemical understanding of transcriptional pausing.